Pengaruh pengetahuan keuangan, pengalaman keuangan, dan pendapatan terhadap perilaku keuangan keluarga - Tirani Rahma Brilianti; Lutfi Lutfi (Journal of Business & Banking, 2019)
This study aims to examine the effect of financial knowledge, financial experience, and income on financial behavior. The sample was taken using a purposive sampling and convenience sampling. The respondents were household financial manager in Madiun. There were 162 people taking part in this study. The data were analyzed using Multiple Regression. The results of this study showed that financial experience and financial knowledge have a significant positive effect on financial behavior. In addition, there is differences in financial behavior based on income level. This implied that household financial managers need to improve their financial knowledge and experience, such as in banking and capita market, so that they are able to manager their families’ financial matter better.